Penerapan E-Government padavOrganisasi Pemerintah dalam Memberikan pelayanan publik yang Efetif dan Efisien terhadap Khalayak Ramai - Saskia Kamaliyyah; Risa Khairiya (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
One aspect that does not escape the reach of the development of technology and information systems is the aspect of government. Where at this time the government is required to be able to run the government system manually and digitally based on technology. One of the actions taken by the government to answer these challenges is to use the implementation of the E-Government system in every government agency or organization. The implementation of E-Government in every government organization is intended so that every official government agency is able to provide effective and efficient public services to the general public, especially being able to provide time and cost efficiency in the process of providing services to the public.